Tree stability in an improved soil to withstand wind loading - Sim, E. K. (2011)
As trees are planted in close proximity to properties and humans in a dense city like Singapore, uprooting of trees can pose safety concerns. Previous research studies have shown that soil properties are important factors that govern tree stability. Soil properties can be improved by mixing top soil (TS) with coarse-grained soil. The effects of soil improvement using coarse-grained soil on tree stability were investigated in this study. Granite chip was used as coarse-grained soil to improve the original top soil. Static analysis and finite element modeling were performed to study tree stability in an improved soil. Factors investigated include root geometry and soil shear strength parameter. Finite element results showed good agreement with static analysis in determining the maximum wind force needed to uproot the tree. Parametric study showed that the wind force needed to uproot the tree was influenced by the mode of failure and the magnitude was dependant on the root geometry and the soil properties. A mixture of 20% top soil and 80% granite chip by dry mass was the optimum mixture for withstanding the maximum wind force needed to uproot the tree.